Atomic study on the interaction between superlattice screw dislocation and γ-Ni precipitate in γ′-Ni3Al intermetallics. (November 2018) - Kondo, Hiromi; Wakeda, Masato; Watanabe, Ikumu
Abstract: Nanoscale γ precipitates in primary microscale γ ′ precipitates of Ni-alloys have been recently observed in experiments. Nanoscale γ precipitates have been one of the potential factors changing the dislocation motion in primary γ ′ precipitates and affecting mechanical properties of Ni-alloys. In this work, the dependency of the interaction between a superlattice screw dislocation and the spherical γ -Ni precipitates in γ ′-Ni3 Al intermetallics on the sizes of the γ precipitate is studied via molecular statics simulations. The calculated external stress, morphology of superlattice screw dislocation, and energy states show that the stress necessary to cut through the precipitate is significantly dependent on the interface between the γ precipitate and γ ′-matrix as well as on the antiphase boundary (APB) energy; the interface between the γ precipitate and γ ′-matrix inhibits the superlattice dislocation during cutting into the γ precipitate, whereas the APB expansion hinders the cut-out action. Among the examined cases, a precipitate of approximately 3 nm in diameter is found to require the largest stress to cut through. We show the origin of interaction between superlattice screw dislocation and γ precipitates in γ ′ matrix from the atomic and energetic perspectives. Highlights: The interaction mechanism between a superlattice screw dislocation and the γ-Ni precipitates in γ'-Ni3Al intermetallics is investigated using molecular statics simulations. The cutting process of the precipitation by the dislocation is compared to some cases of precipitate size. The interface impedes the cut-in behavior of the superlattice dislocation, also the antiphase boundary impedes the cut-out behavior. A precipitate diameter of approximately 3 nm is found to correspond to the maximum pinning force. The origin of the precipitation strengthening is discussed from the atomic and energetic viewpoints.